Evaluation of CD146 as Target for Radioimmunotherapy against Osteosarcoma - Westrøm, Sara; Bønsdorff, Tina B.; Abbas, Nasir; Bruland, Øyvind S.; Jonasdottir, Thora J.; Mælandsmo, Gunhild M.; Larsen, Roy H. (PLOS ONE, 2016)
Background Osteosarcoma is a rare form of cancer but with a substantial need for new active drugs. There is a particular need for targeted therapies to combat metastatic disease. One possible approach is to use an antibody drug conjugate or an antibody radionuclide conjugate to target the osteosarcoma metastases and circulating tumor cells. Herein we have evaluated a radiolabeled monoclonal antibody targeting CD146 both in vitro and in vivo. Methods and Results A murine monoclonal anti-CD146 IgG1 isotype antibody, named OI-3, was developed along with recombinant chimeric versions with human IgG1 or human IgG3 Fc sequences. Using flow cytometry, selective binding of OI-3 to human osteosarcoma cell lines OHS, KPDX and Saos-2 was confirmed. The results confirm a higher expression level of CD146 on human osteosarcoma cells than HER2 and EGFR; antigens targeted by commercially available therapeutic antibodies. The biodistribution of 125I-labeled OI-3 antibody variants was compared with 125I-labeled chimeric anti-EGFR antibody cetuximab in nude mice with subcutaneous OHS osteosarcoma xenografts. OI-3 was able to target CD146 expressing tumors in vivo and showed improved tumor to tissue targeting ratios compared with cetuximab. Subsequently, the three OI-3 variants were conjugated with p-SCN-Bn-DOTA and labeled with a more therapeutically relevant radionuclide, 177Lu, and their biodistributions were studied in the nude mouse model. The 177Lu-labeled OI-3 variants were stable and had therapeutically relevant biodistribution profiles. Dosimetry estimates showed higher absorbed radiation dose to tumor than all other tissues after administration of the chimeric IgG1 OI-3 variant. Conclusion Our results indicate that CD146 can be targeted in vivo by the radiolabeled OI-3 antibodies.